Analysis of the Roles of Project Manager in Organizing Ranking 1 Events at Polbeng Business Expo Chapter Two - Ustamina, Ustamina; Tara Rosa, Nageeta (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of the Project Manager in organizing the Ranking 1 event at the Polbeng Business Expo Chapter Two. This study employs a qualitative approach, utilizing data collection techniques such as interviews, observation, and documentation. Research subjects were selected using purposive sampling, consisting of the core committee, supporting committee, and teachers accompanying the participants. The Project Manager’s role was analyzed based on managerial roles including interpersonal, informational, and decision-making roles as well as the stages of event management: research, design, planning, coordination, and evaluation. The results indicate that the Project Manager plays a significant role in leading the team, assigning tasks according to members’ capabilities, and maintaining effective coordination throughout the event. In the informational aspect, the Project Manager ensures smooth communication flow through meetings, briefings, and digital communication channels, thereby minimizing miscommunication among team members. In addition, in their decision-making role, the Project Manager demonstrated the ability to respond quickly to various challenges, particularly those related to time constraints, resource limitations, and on-site coordination. The event management phases were carried out systematically, although in practice some phases unfolded dynamically. The evaluation phase also identified several areas for improvement. Overall, the Project Manager’s role made a significant contribution to the successful execution of the Ranking 1 event at the Polbeng Business Expo Chapter Two.